A putative glucose-1-phosphate thymidylyltransferase is required for virulence, membrane-associated mechanisms, and tolerance to external stresses in Acidovorax citrulli - Choi, Junhyeok; Lee, Suhyun; Kim, Dohyun; Han, Yoobin; Rhyu, Haerim; Lee, Jisun H.J.; Han, Sang-Wook (Frontiers in Plant Science, 2025)
Glucose-1-phosphate thymidylyltransferase (GptT) is crucial for bacterial cell wall/membrane functions. However, its roles in Acidovorax citrulli (Ac), the causative agent of bacterial fruit blotch (BFB) in watermelon, remain poorly understood. In this study, the roles of GptT in Ac (GptTAc) were elucidated through proteomic and phenotypic analyses using a mutant lacking GptTAc. The virulence of the mutant was remarkably reduced in the germinated-seed inoculation and leaf infiltration. However, its growth, as assessed by optical density (OD) in rich and minimal media, was comparable to that of the wild-type strain. A comparative proteomic analysis combined with clusters of orthologous group classification revealed that GptTAc was related to diverse mechanisms, including motility and the cell wall/membrane. The mutant showed increased lipopolysaccharide production but reduced exopolysaccharide production. Additionally, biofilm formation and auto-aggregation were enhanced, while twitching halo production was diminished. Notably, the mutant was highly susceptible to multiple stress conditions—including ethylenediaminetetraacetic acid, acetic acid, cupric chloride, sodium dodecyl sulfate, and pH stress—as indicated by significantly decreased OD values or colony forming units (CFUs) compared to the wild type. Finally, the mutant strain exhibited significantly higher sensitivity to lysozyme and antibiotics targeting the bacterial cell wall or membrane, as assessed by monitoring OD or CFUs, compared to the wild-type strain. Collectively, these findings suggest that GptTAc is involved in diverse cellular functions, particularly those related to cell wall/membrane integrity. This study provides novel insights into the role of GptTAc in the virulence of Ac, which may facilitate the identification of antivirulence agents targeting GptTAc by screening small-molecule and natural product libraries in order to control BFB.